PENGARUH MARKETING MIX, KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS TOKO ATK 37 PANGKALPINANG) - Marissa, Amanda; Hasianda Tigor, Ryan; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2022)
This research was entitled: “Pengaruh Marketing Mix, Kelengkapan Produk, dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Studi Kasus Toko ATK 37 Pangkalpinang ”. The theory used in this research is Management theory, Marketing theory, Marketing Mix theory. The data collection technique used a questionnaire, with a total of 87 respondents, which was held from March 2022. The variables used are marketing mix variables, product completeness, service quality and purchasing decisions. This study uses an analysis with a quantitative approach to secondary data research in the field. As a tool in statistical data processing used JASP 0.14.1 program. Based on the results of the study that: (1) There is a value (-0.826 > 1.29159 ) then the marketing mix can have a positive and insignificant effect on consumer purchases at ATK 37 Pangkalpinang Stores. (2.) (-0.820 > 1.29159) then the completeness of the product can have a positive and insignificant effect on consumer purchases at ATK 37 Pangkalpinang Stores. (3) (22.603 < 1.29159) then the quality of service can have a positive and significant effect on consumer purchases at 37 Pangkalpinang ATK Stores.